Social phobia: Comments on the viability and validity of an analogue research strategy and british norms for the fear of negative evaluation questionnaire - Stopa, L; Clark, D (2001)
This paper discusses the viability of an analogue research design for studying key processes in social phobia by comparing individuals who score high and low on the Fear of Negative Evaluation Scale (FNE: Watson and Friend, 1969). Research indicates remarkable consistency in the processes that distinguish patients with social phobia from controls and high FNE volunteers from low FNE volunteers. Unfortunately, all existing FNE norms are based on North American populations. The present paper presents British student norms and suggests possible cut-off points for defining groups for analogue research. Advantages of the analogue strategy include rapid piloting of new paradigms and the use of more complex experimental designs that require substantial sample sizes. Limitations of analogue research are also highlighted.